Kontribusi Kinerja Guru, Sarana Prasarana, Dan Layanan Administrasi Terhadap Kepuasan Siswa Di Sman 2 Sukoharjo - WULANDARI, SUSI, Dr. SUYATMINI M.Si (2017)
The present research aims at analysing the contribution of teacher performance, infrastructure and administration service to Student Satisfaction at SMAN 2 Sukoharjo either simultaneously or partially. This research is a quantitative research with correlation research design. Researcher conducts this research at SMAN 2 Sukoharjo in the first semester of the academic year 2016/2017. The technique of Sampling in this research uses proportional random sampling technique with a sample of 92 students. Researcher uses a questionnaire techniques and observation as a data collecting technique. In data analysing, researcher the hypotheses test after the classical assumption test. There are four findings from this research. (1) There are 55,8% contribution of teacher performance, infrastructure and administrationon service collectively to Student Satisfaction. (2) There are 16,55% of teacher performance to student satisfaction. (3) There are 23,82% contribution of infrastructure to student satisfaction. (4) There are 15,44% contribution of administration service to student satisfaction. Key words: satisfaction, student, performance, infrastructure, administration